IMPLEMENTASI PEMBIASAAN IBADAH DAN BUDAYA KANTIN KEJUJURAN DALAM MENANAMKAN NILAI-NILAI AKIDAH DAN AKHLAK SISWA DI SMP NAMIRA KOTA PROBOLINGGO - Ni'mah, Lailatun; Devy Habibi Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of worship habits and the honesty canteen culture instilling faith and moral values ​​in students at Namira Junior High School in Probolinggo City. The research approach used was qualitative with a descriptive approach, using data collection techniques such as observation, in-depth interviews, and documentation. The results indicate that worship habits, such as congregational Dhuha and Dhuhur prayers, play a significant role in fostering spiritual discipline, religious responsibility, and ongoing awareness of worship. The honesty canteen culture serves as an effective character education medium for instilling the values ​​of honesty, trustworthiness, and social integrity among students. The synergy of these two activities creates a religious environment conducive to the comprehensive internalization of faith and moral values. Thus, worship habits and the honesty canteen culture have proven to be applicable and relevant Islamic educational strategies for strengthening the religious and moral character of students in the modern era.